The Impact of Logistics Services On The E-Shoppers' Satisfaction - Salini Devi Rajendran; Siti Norida Wahab; Yeow Way Ling; Lim Shin Yun (International Journal of Supply Chain Management, 2018)
In a digital era, E-commerce is fast-growing industry. People never thought to live without E-commerce. A day without E-commerce would be complicated, inconvenience and impossible. There are many components in online shopping market that play important roles in satisfying online shoppers. One of it is logistics services which influence online shoppers satisfaction level. Thus, this study mainly explore how logistics services may influences online shoppers satisfaction level. The specific aim of this paper is to determine the main logistics services elements that influences satisfaction of online shoppers. A total of 178 respondents who have experienced in online shopping were interviewed face-to-face using a structured questionnaire. Pearson correlation and multiple regression were used to analyze the data. The findings from the study revealed that service recovery, delivery service and customer service were the factors positively influencing the satisfaction level of E-commerce shoppers. The results of this study would helpful for online retailers to identify ways for improvement of their services especially from logistics perspective that eventually will enhance shoppers loyalty and enhance satisfaction.